Analysing political deception: The virtues of Bernard Williams' anti‐tyranny argument. (24th April 2018) - Cross, Ben
Abstract: According to Bernard Williams' "anti‐tyranny argument, " it is important for citizens to have access to true information about the exercise of political power in order to check the tendency of governments and politicians to become tyrannous. Although Williams thinks the argument is one of the better arguments for the importance of truthfulness in politics, he acknowledges 2 limitations. First, it appears to offer little more than the truism that tyranny is a bad thing—a truism that will be accepted by all but tyrants themselves. Second, it may not offer any reasons for the importance of true information about forms of political power, which do not seem tyrannous. I argue that kind of political analysis required to apply the anti‐tyranny argument enables it to overcome both limitations. In so doing, I show that it has a clear advantage over rival arguments for the importance of truthfulness in politics.